Intraoperative lung ultrasound: A clinicodynamic perspective - Amit Kumar Mittal; Namrata Gupta (Wolters Kluwer Medknow Publications, 2016)
In the era of evidence-based medicine, ultrasonography has emerged as an important and indispensable tool in clinical practice in various specialties including critical care. Lung ultrasound (LUS) has a wide potential in various surgical and clinical situations for timely and easy detection of an impending crisis such as pulmonary edema, endobronchial tube migration, pneumothorax, atelectasis, pleural effusion, and various other causes of desaturation before it clinically ensues to critical level. Although ultrasonography is frequently used in nerve blocks, airway handling, and vascular access, LUS for routine intraoperative monitoring and in crisis management still necessitates recognition. After reviewing the various articles regarding the use of LUS in critical care, we found, that LUS can be used in various intraoperative circumstances similar to Intensive Care Unit with some limitations. Except for few attempts in the intraoperative detection of pneumothorax, LUS is hardly used but has wider perspective for routine and crisis management in real-time. If anesthesiologists add LUS in their routine monitoring armamentarium, it can assist to move a step ahead in the dynamic management of critically ill and high-risk patients.